Clemens William (“Clem”) Pratt 2 July 1936–16 January 2025 - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2025)
This paper is an appreciation of the life and contributions of Dr C. W. (Clem) Pratt, who died in January 2025. He had a 38-year career with the PMG’s Department and its successors, working first on traffic engineering and then expanding his career and interests into computing and operational support systems. He was a Distinguished Fellow of the Telecommunications Society of Australia, having been Vice-Chairman of the National Board for 17 years. He was active in the Statistical Society of Australia, serving as national Chairman for one term. He was a long-term member of the Advisory Council for the International Teletraffic Congresses and an influential educator on teletraffic engineering and related statistical methods.